Efektivitas Tabata terhadap Kebugaran Mahasiswa Pendidikan Kepelatihan Olahraga - Azizah, Nisa Hamidah Nur; Pramono, Bayu Agung; Muhammad, Muhammad; Fajar, Muhammad Kharis; Azriddin, Adlina Dayana Binti (Faculty of Sport and Health Sciences, 2023)
Sports physical training is a physical activity that has a good effect on health, fitness and performance. Currently, many physical exercises have been developed, especially physical exercises using high intensity. The purpose of this study was to see the effects of high-intensity training on fitness and health in Sports Coaching Education students. In this study, the experimental pre-test post-test method was used involving seven untraining men and nine training men who are students majoring Sports Coaching Education (SCE). This study was conducted in four weeks, with frequency three times a week. The test used is the Shapiro-Wilk for normality check and Wilcoxon test to see the difference in pre-test and post-test after the sample gets high-intensity training treatment for four weeks. The results of this study showed differences in post HR Max, post bodyweight, post BMI, post sum recovery, and post HR rest (p<0.05). On the results of N-gain, tabata training was quite effective given to the group of training students than the untraining group. The conclusion in this study shows that the application of high-intensity training requires an adaptation process in the unfit student group to have a positive effect on the health and fitness of SCE students.